2005
DOI: 10.3208/sandf.45.4_13
|View full text |Cite
|
Sign up to set email alerts
|

A Reconsideration of the Safety of Piled Bridge Foundations in Liquefiable Soils

Abstract: The collapse of piled foundations in liquefiable soil has been observed in the majority of recent strong earthquakes. This paper critically reviews the current understanding of pile failure in liquefiable deposits, making reference to modern design codes such as JRA (1996), and taking the well-documented failure of the Showa Bridge in the 1964 Niigata earthquake as an example of what must be avoided. It is shown that the current understanding cannot explain some observations of pile failure. The current method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 9 publications
(12 reference statements)
0
30
0
1
Order By: Relevance
“…This aspect is further explored by the study of the pile failure of Showa Bridge during the Niigata earthquake of 1964 in the next section. More details of this study can be found in Bhattacharya et al (2005). The actual axial load in the pile has been calculated by considering the dead load of the superstructure.…”
Section: Interaction Formula To Account For Plastic Bucklingmentioning
confidence: 99%
“…This aspect is further explored by the study of the pile failure of Showa Bridge during the Niigata earthquake of 1964 in the next section. More details of this study can be found in Bhattacharya et al (2005). The actual axial load in the pile has been calculated by considering the dead load of the superstructure.…”
Section: Interaction Formula To Account For Plastic Bucklingmentioning
confidence: 99%
“…Because the soil stiffness may change due to pore water pressure generation, numerous researches have been carried out to evaluate p-y curves for piles in liquefiable soils, such as Dobry et al (1995), Yasuda et al (1998), RTRI (1999), AIJ (2001), Takahashi et al (2002) and Rollins et al (2005). Bhattacharya et al (2005) suggested an S-curve shape of the 'p-y' curve for liquefied soil. Maheshwari and Sarkar (2011) and Sarkar and Maheshwari (2012) used the Drucker-Prager soil model of work hardening to investigate the 3D behaviour of single piles and pile groups.…”
Section: P-y Curves For Modelling Liquefiable Soilsmentioning
confidence: 99%
“…As a result, the behaviour of piled foundations during liquefaction remains an area of active research (Haigh, 2002;Bhattacharya, 2003;Bhattacharya et al, 2004Bhattacharya et al, , 2005aBhattacharya et al, , 2005bCubrinovski et al, 2006;Knappett & Madabhushi, 2009;Dash et al, 2010;Madabhushi et al, 2010;Stringer & Madabhushi, 2012;Lombardi, 2013;Lombardi & Bhattacharya, 2014a.…”
Section: Introductionmentioning
confidence: 99%